Does an enhanced recovery integrated care pathway (ICP) encourage adherence to prescribing guidelines, accelerate postoperative recovery and reduce the length of stay for gynaecological oncology patients?. (April 2013) - Letton, C.; Cheung, C.; Nordin, A.
<x xml:space="preserve">Abstract</x> A new integrated care pathway (ICP) proforma for gynaecological oncology patients was developed and introduced in early 2010. The ICP is a goal-defined and time-specified documentation by gynaecological oncology doctors and nurses, guided by certain parameters to be achieved in pre and postoperative days. All patients were admitted to the same unit and underwent a major abdominal/pelvic procedure for confirmed or suspected gynaecological malignancy, including hysterectomy and oophorectomy. The control group included 58 randomly selected patients from May 2008 to March 2009 and the intervention group comprised 52 patients, after the introduction of the ICP. The effectiveness was assessed with a variety of measurements: the duration of intraperitoneal drains, urethral catheters and intravenous fluids postoperatively; time taken for the patient to eat and drink; time taken to mobilisation; and the total length of stay in hospital. We also assessed whether the implementation of the care pathway was associated with an increase in adherence to prescribing guidelines for thromboprophylaxis and postoperative antibiotics and sodium docusate. The new ICP encouraged clearer documentation and regular review of fluids, drains and catheters. There was a modest reduction in the length of stay and an increase in prescribed thromboprophylaxis and sodium docusate (Cheung et al. 2011).